Penerapan Metode Index Card Match Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam - gina Risgiantana; nenden munawaroh; masripah (Advances In Education Journal, 2024)
This research aims to analyze the results of applying the index card match method in Islamic religious education learning because the background to this research is the low learning outcomes of students in Islamic religious education subjects which are caused by learning methods that are less varied and seem monotonous at SMAN 8 GARUT. In this study, a pretest and posttest were carried out to determine the results before and after treatment. Accompanied by other techniques of observation, interviews and documentation. The aim of this research is to determine student learning outcomes when they have been treated with different learning models, then to change the passive character of students when carrying out teaching and learning activities and improve student learning outcomes in educational subjects. Islamic religion. This research includes the principles of quantitative research methods. Experiments using a Quasi nonequivalent Control Group design where this research was carried out in order to obtain more accurate results. Based on the calculation results, it can be concluded that to test the success of improving learning outcomes through the application of the index card match method using 20 questions, 16 of which are valid, and the reliability test is 0.39. The pretest normality result in the experimental class was 59.9 and the control class 66.5, while the posttest normality result in the experimental class was 77 and the control class was 76. The results of the hypothesis tester showed that the proposed hypothesis was acceptable because the calculated T was greater than the T table, namely 3.31% > 2.66. After implementing the index card match method, there was an increase in student learning outcomes in Islamic religious education learning.